(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aimed to identify the level of job satisfaction of teachers in secondary schools in Tartous governorate, as well as their level of job performance, and to identify the impact of job satisfaction on the performance of the sample members. The descriptive approach was used. The sample included (440) teachers, ie (88.53%) of the original community of the selected schools, for the Academic year 2016/2017. In order to achieve the objective of the research, two questionnaires were designed, The first one consisted of (37) sections divided into five axes to measure job satisfaction. The second consisted of (29) items to measure the job performance. The research reached several results, most importantly: job satisfaction of the sample members came at medium level, and the axis of The nature of work) ranked first, While the axis of (work environment) ranked last. As well as job performance of the sample members came at medium degree with average of (3,31) and a relative weight (67,54). The result also shown The effect of job satisfaction on job performance of the sample members. The research presented some of conclusions and proposals, including: provide an emotive and lovely atmosphere for teachers to enable them to perform their tasks to the fullest, and improve the work environment by providing educational equipment and tools to facilitate the work of teaching, as well as conducting similar studies in other educational stages and in other governorate.